KEANEKARAGAMAN TUMBUHAN LIANA DI HUTAN BULLA KECAMATAN UMALULU KABUPATEN SUMBA TIMUR - Orfi Randjamandi; Yohana Makaborang; Anita Tamu Ina (Universitas Pakuan, 2022)
The purpose of this study was to determine the diversity of lianas in the Bulla Forest, Umalulu District, East Sumba Regency. Sampling at the research site using a combined method (belt transect). The data obtained were analyzed using a quantitative descriptive approach with the Shanon Wiener diversity index formula. Plant samples were calculated using a quadratic transect with a plot size of 5 x 5 meters with a distance between them of15 meters placed perpendicular to the line towards a depth of 100 meters using a plot of 15 plots. Environmental factors measured were soil pH, humidity and air temperature. Measurements were made at each observation station. The results obtained 12 species consisting of Piper betle L., Dioscorea alata L., Paederia scandens L. Piper caducibracteum, Connarus semidecandrum jack, Smilax lasioneura, Cyclea barbata, Vitis quadrangula, Gynura procumbens (Lour.) merr., Melothria pendula L., Odontacarya truncata, and Cocculus carolinus L. The diversity index obtained was in the moderate category with a value of H' = 1.894.